A prospective evaluation of ultrasound as a diagnostic tool in acute microcrystalline arthritis. Issue 1 (December 2015) - Zufferey, Pascal; Valcov, Roxana; Fabreguet, Isabelle; Dumusc, Alexandre; Omoumi, Patrick; So, Alexander
Abstract Introduction The performance of ultrasound (US) in the diagnosis of acute gouty (MSU) arthritis and calcium pyrophosphate (CPP) arthritis is not yet well defined. Most studies evaluated US as the basis for diagnosing crystal arthritis in already diagnosed cases of gout and few prospective studies have been performed. Methods One hundred nine consecutive patients who presented an acute arthritis of suspected microcrystalline arthritis were prospectively included. All underwent an US of the symptomatic joints(s) and of knees, ankles and 1st metatarsopalangeal (MTP) joints by a rheumatologist "blinded" to the clinical history. 92 also had standard X-rays. Crystal identification was the gold standard. Results Fifty-one patients had MSU, 28 CPP and 9 had both crystals by microscopic analysis. No crystals were detected in 21. One had septic arthritis. Based on US signs in the symptomatic joint, the sensitivity of US for both gout and CPP was low (60 % for both). In gout, the presence of US signs in the symptomatic joint was highly predictive of the diagnosis (PPV = 92 %). When US diagnosis was based on an examination of multiple joints, the sensitivity for both gout and CPP rose significantly but the specificity and the PPV decreased. In the absence of US signs in all the joints studied, CPP arthritis was unlikely (NPV = 87 %) particularly in patients with no previous crisis (NPV = 94 %). X-ray of the symptomatic joints was confirmed to be not useful in diagnosing gout and was equally sensitive or specific as US in CPP arthritis. Conclusions Arthrocenthesis remains the key investigation for the diagnosis of microcrystalline acute arthritis. Although US can help in the diagnostic process, its diagnostic performance is only moderate. US should not be limited to the symptomatic joint. Examination of multiple joints gives a better diagnostic sensitivity but lower specificity.